2016
DOI: 10.1161/strokeaha.116.013306
|View full text |Cite
|
Sign up to set email alerts
|

Permeable Thrombi Are Associated With Higher Intravenous Recombinant Tissue-Type Plasminogen Activator Treatment Success in Patients With Acute Ischemic Stroke

Abstract: Early complete recanalization of an occluded artery is a strong predictor of favorable functional outcome in patients with acute ischemic stroke.1 To increase the chance of favorable outcome, guidelines recommend the use of intravenous thrombolysis with recombinant tissue-type plasminogen activator (r-tPA) in eligible patients.2 Because intravenous r-tPA treatment results in a relatively low rate of recanalization, 3 it might be useful to estimate the likelihood of failure or success of intravenous r-tPA befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
59
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 21 publications
5
59
3
Order By: Relevance
“…Moreover, thrombus permeability is also associated with better clinical outcome in their study. Santos et al 8 thus substantiate previous evidence about thrombus porosity identified using such imaging constructs like residual flow through thrombus on CT angiography and occult anterograde flow through thrombus on CT perfusion that are imaging markers of early thrombus lysis with alteplase. 3,7 Other imaging constructs like thrombus location on CTA and Trans-cranial Doppler, thrombus length on noncontrast CT and CTA, clot burden score on CTA, forward flow through clot on dynamic CTA, collateral status on CTA and CT perfusion, Gradient Echo blooming on magnetic resonance imaging have all been shown to be markers of thrombus lysis with alteplase.…”
Section: See Related Article P 2061supporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, thrombus permeability is also associated with better clinical outcome in their study. Santos et al 8 thus substantiate previous evidence about thrombus porosity identified using such imaging constructs like residual flow through thrombus on CT angiography and occult anterograde flow through thrombus on CT perfusion that are imaging markers of early thrombus lysis with alteplase. 3,7 Other imaging constructs like thrombus location on CTA and Trans-cranial Doppler, thrombus length on noncontrast CT and CTA, clot burden score on CTA, forward flow through clot on dynamic CTA, collateral status on CTA and CT perfusion, Gradient Echo blooming on magnetic resonance imaging have all been shown to be markers of thrombus lysis with alteplase.…”
Section: See Related Article P 2061supporting
confidence: 68%
“…3,7 Other imaging constructs like thrombus location on CTA and Trans-cranial Doppler, thrombus length on noncontrast CT and CTA, clot burden score on CTA, forward flow through clot on dynamic CTA, collateral status on CTA and CT perfusion, Gradient Echo blooming on magnetic resonance imaging have all been shown to be markers of thrombus lysis with alteplase. [2][3][4][5][6][7][8] Taken together, this growing body of literature is helping treating physicians who predict the likelihood of treatment success with alteplase in patients with acute ischemic stroke.…”
Section: See Related Article P 2061mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] It has been suggested that thrombus permeability might be related to the physical porosity of thrombus and might reflect the ability of soluble molecules to move within the gaps among adjacent platelets, fibrin filaments, and red blood cells. 8,9,12,13 Preclinical studies have demonstrated that high permeability of the thrombus within the occluded artery allowed residual blood to flow through the thrombus, 9,10 which may have a positive effect on neurologic outcome after acute ischemia due to the compensating oxygenation of brain tissue distal to the occluded artery. Recently, thrombus attenuation increase (TAI) was used to assess the thrombus permeability on conventional single-phase CT angiography and noncontrast CT. A pervious thrombus with a high TAI was found to be associated with better neurologic outcome after reperfusion therapy in patients with AIS.…”
mentioning
confidence: 99%
“…Recently, thrombus attenuation increase (TAI) was used to assess the thrombus permeability on conventional single-phase CT angiography and noncontrast CT. A pervious thrombus with a high TAI was found to be associated with better neurologic outcome after reperfusion therapy in patients with AIS. 8,12 The enhancement of arteries on conventional single-phase CTA is affected by the acquisition time because the contrast filling of the occlusion site is delayed compared with that in the normal condition. 14 Therefore, the permeability of the thrombi may be underestimated if single-phase CTA is acquired before contrast completely penetrates the thrombus.…”
mentioning
confidence: 99%